2016
DOI: 10.1109/tc.2015.2419669
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Fine-Grained Heterogeneity with Composite Cores

Abstract: Heterogeneous multicore systems-comprising multiple cores with varying performance and energy characteristicshave emerged as a promising approach to increasing energy efficiency. Such systems reduce energy consumption by identifying application phases and migrating execution to the most efficient core that meets performance requirements. However, the overheads of migrating between cores limit opportunities to coarse-grained phases (hundreds of millions of instructions), reducing the potential to exploit energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…One limitation from this approach is that the core operation is mutually exclusive. However, this is deliberate for our limit study as we are interested in single thread behaviour and it resembles the operation of the rst commercial HMP systems [6] and merged cores that share the front end [20,22,24]. e infrastructure can easily be extended to accommodate beyond for more than one pair of coupled cores, however the decision tree of migration combinations is signi cantly more complex and is beyond the scope of this paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One limitation from this approach is that the core operation is mutually exclusive. However, this is deliberate for our limit study as we are interested in single thread behaviour and it resembles the operation of the rst commercial HMP systems [6] and merged cores that share the front end [20,22,24]. e infrastructure can easily be extended to accommodate beyond for more than one pair of coupled cores, however the decision tree of migration combinations is signi cantly more complex and is beyond the scope of this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work on the existence of phases at ne granularity and their potential micromanagement has shown that it is possible to exploit their bene ts through a heterogeneous system with di erent back-ends sharing the same front end [12,[20][21][22]. Despite the claim, no experimental data is provided that reveals the actual existence of application phases that appear at a ne granularity nor are the circumstances under which they can be exploited explained.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, leading studies in the literature try to select an appropriate core in multicore systems based on the needs of running applications [6], [9], [10]. Another area of research is based on architectural techniques to achieve similar performance figures of out-of-order processors with the help of simpler datapath structures requiring less power and area [2], [11], [12], [13], [14], [15], [16].…”
Section: Related Workmentioning
confidence: 99%
“…Purely dynamic approaches take into account runtime information. They can be implemented at the architecture level [13,17,25,30,33], or at the virtual Figure 10. Time (Top) and Energy (Bottom) comparison between Astro and GTS (G).…”
Section: Related Workmentioning
confidence: 99%